A Model for the Education of Gifted Learners in Lebanon - Sarouphim, Ketty M. (2010)
The purpose of this paper is to present a model for developing a comprehensive system of education for gifted learners in Lebanon. The model consists of three phases and includes key elements for establishing gifted education in the country, such as raising community awareness, adopting valid identification measures, and developing effective curricula. An important consideration is to embed the model in non-traditional views of intelligence and giftedness so that programs are diversified and identification is not limited to high scores on standardized tests. As such, the model is based on DISCOVER, a non-traditional system for identifying and educating gifted learners. Research is needed to determine the effectiveness of such a model for Lebanon. The model could be emulated by other Arab countries where it can be adopted and adapted to the unique needs and particulars of each culture.